1998
DOI: 10.1046/j.1365-2672.1997.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell membrane integrity and lysis in Lactococcus lactis: the detection of a population of permeable cells in post-logarithmic phase cultures

Abstract: A method was developed that enabled an analysis of the proportion of permeable cells in a culture of Lactococcus lactis. This used the fluorescence of propidium iodide (PI) when in contact with DNA and the impermeability of the intact cell membrane to this compound. A permeability index was suggested that expresses the PI‐induced fluorescence of a cell suspension as a percentage of the value obtained from wholly permeabilized cells after treatment with cetyltrimethylammonium bromide. This method was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 3 publications
2
47
0
1
Order By: Relevance
“…Phenotypes of the resulting MG1363yjgB, MG1363acmByjgB, and MG1363acmAacmByjgB mutants (Table 1) were analyzed by a number of custom assays used for characterization of pepti- (17). These included analysis of cellular growth rate, measurement of cell autolysis in the stationary phase both by decrease in optical density and by activity of concomitantly released intracellular peptidase PepX, and analysis of membrane permeabilization in the stationary phase with the fluorescent DNA marker propidium iodide (25). The assays demonstrated no visible phenotypic change associated with yjgB inactivation in either of the created mutants compared to the wild type (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypes of the resulting MG1363yjgB, MG1363acmByjgB, and MG1363acmAacmByjgB mutants (Table 1) were analyzed by a number of custom assays used for characterization of pepti- (17). These included analysis of cellular growth rate, measurement of cell autolysis in the stationary phase both by decrease in optical density and by activity of concomitantly released intracellular peptidase PepX, and analysis of membrane permeabilization in the stationary phase with the fluorescent DNA marker propidium iodide (25). The assays demonstrated no visible phenotypic change associated with yjgB inactivation in either of the created mutants compared to the wild type (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the membrane permeability of L. lactis was measured with PI and carboxyfluorescein diacetate (cFDA) using spectrofluorimetry and fluorescence microscopy in a study of viability after various stress treatments (6). Also, permeable fractions in post-logarithmic-phase cultures of L. lactis were measured with PI using spectrofluorimetry (22). Finally, permeabilization by bile salts and acid with concomitant cell death of various lactic acid bacteria was measured with PI, TOTO-1, and cFDA (5).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative methodologies for extraction such as using a cheese press and using hypertonic buffers have been tried (30). However, to date no really good method is available, and an understanding of the role of lysis in cheese ripening is still lacking (8,22).…”
mentioning
confidence: 99%
“…Effect on Bacterial Membrane Integrity and Growth. The effect of 200 nM amine-and carboxyl-PEG-QDs on cell membrane integrity was probed by FCM using PI, a fluorescent nucleic acid stain that does not penetrate cells with intact membranes, while staining cells with damaged or leaky membranes (34). FCM analysis of PI treated cells demonstrated that both amine-and carboxyl-PEG-QDs induce an increase in the number of damaged/leaky membranes of C. metallidurans cells (Figure 3).…”
Section: Mops)mentioning
confidence: 99%